Evidence-Based Ruminal Microbiota (Alimentos Ciencia e Ingeniería, 2022)
Ruminants break down the fiber of the feed intake in the rumen through a microbial symbiosis, which performs its enzymatic hydrolysis and subsequent fermentation. The objective was demonstrating the activity of rumen microorganisms consisting of bacteria, protozoa, fungi and methanogenic archaea. Bacterial populations are located at three different levels in the rumen: attached to the solid. The concentration of bacteria in the rumen is higher than that of protozoa. Protozoa support a fundamental role in fiber degradation, store large amounts of starch and slow down the production of acids that reduce rumen pH. Fungi have an important function in the digestion of the cell walls of plants, especially those of low quality. Archaea in the rumen are strictly anaerobic microorganisms and produce methane from CO2 and hydrogen. Conclusion: Rumen microorganisms establish complex relationships among themselves, which allow the degradation of the feed that reaches the rumen and consequently the use of the nutrients it contains.